Single-Dose Intraventricular Nimodipine Microparticles Versus Oral Nimodipine for Aneurysmal Subarachnoid Hemorrhage. - Carlson, Andrew P.; Haenggi, Daniel; Wong, George K.; Etminan, Nima; Mayer, Stephan A.; Aldrich, Francois; Diringer, Michael N.; Schmutzhard, Erich; Faleck, Herbert J.; Ng, David; Saville, Benjamin R.; Bleck, Thomas; et al. (Stroke, 2020)
Background and Purpose- EG-1962 is a sustained release formulation of nimodipine administered via external ventricular drain in patients with aneurysmal subarachnoid hemorrhage. A randomized, open-label, phase 1/2a, dose-escalation study provided impetus for this study to evaluate efficacy and safety of a single intraventricular 600 mg dose of EG-1962 to patients with aneurysmal subarachnoid hemorrhage, compared with standard of care oral nimodipine. Methods- Subjects were World Federation of Neurological Surgeons grades 2-4, modified Fisher grades 2-4 and had an external ventricular drain inserted as part of standard of care. The primary end point was the proportion of subjects with favorable outcome at day 90 after aneurysmal subarachnoid hemorrhage (extended Glasgow outcome scale 6-8). The proportion of subjects with favorable outcome at day 90 on the Montreal cognitive assessment, as well as the incidence of delayed cerebral ischemia and infarction, use of rescue therapy and safety were evaluated. Results- The study was halted by the independent data monitoring board after planned interim analysis of 210 subjects (289 randomized) with day 90 outcome found the study was unlikely to achieve its primary end point. After day 90 follow-up of all subjects, the proportion with favorable outcome on the extended Glasgow outcome scale was 45% (65/144) in the EG-1962 and 42% (62/145) in the placebo group (risk ratio, 1.01 [95% CI, 0.83-1.22], P=0.95). Consistent with its mechanism of action, EG-1962 significantly reduced vasospasm (50% [69/138] EG-1962 versus 63% [91/144], P=0.025) and hypotension (7% [9/138] versus 10% [14/144]). Analysis of prespecified subject strata suggested potential efficacy in World Federation of Neurological Surgeons 3-4 subjects (46% [32/69] EG-1962 versus 32% [24/75] placebo, odds ratio, 1.22 [95% CI, 0.94-1.58], P=0.13). No safety concerns were identified that halted the study or that preclude further development. Conclusions- There was no significant increase in favorable outcome for EG-1962 compared with standard of care in the overall study population. The safety profile was acceptable. Registration- URL: https://www.clinicaltrials.gov; Unique identifier: NCT02790632.
EVALuna2:280008